Allium sativum L. Improves Visual Memory and Attention in Healthy Human Volunteers - Bin Sayeed, Muhammad Shahdaat; Shahriar, Mohammad; Islam, Sardar Mohd. Ashraful; Hossain, Md. Monir; Bari, Md. Sazzadul; Haque, Parsa Sanjana; Tasnim, Sara; Bhuiyan, Mohiuddin Ahmed (Evidence-based complementary and alternative medicine, 2015)
Studies have shown that Allium sativum L. (AS) protects amyloid-beta peptide-induced apoptosis, prevents oxidative insults to neurons and synapses, and thus prevent Alzheimer’s disease progression in experimental animals. However, there is no experimental evidence in human regarding its putative role in memory and cognition. We have studied the effect of AS consumption by healthy human volunteers on visual memory, verbal memory, attention, and executive function in comparison to control subjects taking placebo. The study was conducted over five weeks and twenty volunteers of both genders were recruited and divided randomly into two groups: A (AS) and B (placebo). Both groups participated in the 6 computerized neuropsychological tests of the Cambridge Neuropsychological Test Automated Battery (CANTAB) twice: at the beginning and after five weeks of the study. We found statistically significant difference ( p < 0.05 ) in several parameters of visual memory and attention due to AS ingestion. We also found statistically nonsignificant ( p > 0.05 ) beneficial effects on verbal memory and executive function within a short period of time among the volunteers. Study for a longer period of time with patients suffering from neurodegenerative diseases might yield more relevant results regarding the potential therapeutic role of AS.